The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1158/0008-5472.can-05-2384
|View full text |Cite
|
Sign up to set email alerts
|

Combinational FLt3 Ligand and Granulocyte Macrophage Colony-Stimulating Factor Treatment Promotes Enhanced Tumor Infiltration by Dendritic Cells and Antitumor CD8+ T-Cell Cross-priming but Is Ineffective as a Therapy

Abstract: Dendritic cells play significant roles in the development and maintenance of antitumor immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…Recently, it was reported that combination treatment of mice bearing established tumors with FltL3 and GM-CSF proteins resulted in the recruitment of large numbers of tumorinfiltrating DC and induction of a CD8 þ T-cell-mediated immune response. 36 Mouse splenic DC could be expanded by intramuscular delivery of either Flt3L or GM-CSF cDNA. 11 However, a more potent T-cell proliferation was observed in the mixed lymphocyte reaction when stimulator DC originated from mice treated with Flt3L cDNA, compared Figure 7 Induction of cell-mediated immunity in mice vaccinated with pN-neu combined with pFLAG or pFL/pGM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that combination treatment of mice bearing established tumors with FltL3 and GM-CSF proteins resulted in the recruitment of large numbers of tumorinfiltrating DC and induction of a CD8 þ T-cell-mediated immune response. 36 Mouse splenic DC could be expanded by intramuscular delivery of either Flt3L or GM-CSF cDNA. 11 However, a more potent T-cell proliferation was observed in the mixed lymphocyte reaction when stimulator DC originated from mice treated with Flt3L cDNA, compared Figure 7 Induction of cell-mediated immunity in mice vaccinated with pN-neu combined with pFLAG or pFL/pGM.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, we observed that the treatment of mice bearing syngeneic CMS4 sarcomas with rFLt3 ligand (rFL) plus recombinant GM-CSF (rGM-CSF) resulted in the markedly enhanced cross-priming of anti-CMS4 CD8 ϩ T cells in vivo (26). However, these responses yielded no meaningful impact on tumor growth, despite the infiltration of significant numbers of tumorspecific CD8 ϩ T cells into tumor lesions.…”
Section: T He Cd8mentioning
confidence: 99%
“…CMS4 sarcoma (H-2 d ) cells were cultured, and s.c. tumors were established and monitored for growth in syngeneic BALB/cJ mice, as previously described (26).…”
Section: Tumor Establishmentmentioning
confidence: 99%
See 2 more Smart Citations